2013
DOI: 10.1002/fuce.201300002
|View full text |Cite
|
Sign up to set email alerts
|

Niobium Dioxide Facilitating Methanol Electrooxidation on Pt/C Catalyst by Synergistic Effect

Abstract: In this work, Pt nanoparticles are deposited on NbO2‐modified carbon composites and evaluated as promising direct methanol fuel cell (DMFC) electrocatalysts. Transmission electron microscopy (TEM) and X‐ray diffraction (XRD) indicate that Pt nanoparticles (about 2.5 nm) are uniformly dispersed on NbO2‐modified carbon composites. Electrochemical measurements show that the mass activity toward methanol electrooxidation on Pt/NbO2‐C is as high as 3.0 times that of conventional Pt/C. Meanwhile, the onset potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 39 publications
(46 reference statements)
0
6
0
Order By: Relevance
“… Carbon-supported metal oxide structure can effectively improve the defect of poor conductivity of MoO x and enhance the electron transmission efficiency during the reaction The anchoring effect of MoO x prevents the aggregation of PtNi nanoparticles and shedding of catalyst particles due to the corrosion of the carbon support, improving the durability. , Nitrogen doping can change the surface electronic properties of the carbon support and increase the defect sites (i.e., catalytically active sites), thereby improving the catalytic activity. Besides, the Ni–N bond and nitrogen doping effect can also stabilize Ni in the alloy and the interaction between nanoparticles and supports and thus improve the durability. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Carbon-supported metal oxide structure can effectively improve the defect of poor conductivity of MoO x and enhance the electron transmission efficiency during the reaction The anchoring effect of MoO x prevents the aggregation of PtNi nanoparticles and shedding of catalyst particles due to the corrosion of the carbon support, improving the durability. , Nitrogen doping can change the surface electronic properties of the carbon support and increase the defect sites (i.e., catalytically active sites), thereby improving the catalytic activity. Besides, the Ni–N bond and nitrogen doping effect can also stabilize Ni in the alloy and the interaction between nanoparticles and supports and thus improve the durability. …”
Section: Resultsmentioning
confidence: 99%
“…The anchoring effect of MoO x prevents the aggregation of PtNi nanoparticles and shedding of catalyst particles due to the corrosion of the carbon support, improving the durability. , …”
Section: Resultsmentioning
confidence: 99%
“…It can be concluded that there is an interaction between Pt and NbO 2 , and the strong metal‐support interaction weakens the chemisorption of OH groups on the surface of the Pt active sites, thereby inhibiting the formation of Pt‐O bands and thus improving the ORR performance. The lateral repulsion between OH ads or O 2ads of Pt active sites and OH ads species on NbO 2 surface can weaken Pt‐O bond and release Pt active sites, which is particularly critical for an excellent ORR electrocatalyst , . All these strong interactions can form the unique TPB structure to produce some possible synergetic effect between Pt, graphene and NbO 2 , which is beneficial to provide the path of electron transfer among Pt, NbO 2 and graphene, thus effectively enhance the electrochemical activity and stability.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 12 shows the schematic illustrations of the special TPB structure in Pt-NbO 2 -graphene electrocatalyst, and the pro-posed ORR mechanism. It can be concluded that there is an interaction between Pt and NbO 2 , and the strong metal-support interaction weakens the chemisorption of OH groups on the surface of the 27]. All these strong interactions can form the unique TPB structure to produce some possible synergetic effect between Pt, graphene and NbO 2 , which is beneficial to provide the path of electron transfer among Pt, NbO 2 and graphene, thus effectively enhance the electrochemical activity and stability.…”
Section: Electrochemical Behaviors Of Electrocatalystsmentioning
confidence: 99%
See 1 more Smart Citation